2015
DOI: 10.1038/ncomms10306
|View full text |Cite
|
Sign up to set email alerts
|

Atomic scale simulation of carbon nanotube nucleation from hydrocarbon precursors

Abstract: Atomic scale simulations of the nucleation and growth of carbon nanotubes is essential for understanding their growth mechanism. In spite of over twenty years of simulation efforts in this area, limited progress has so far been made on addressing the role of the hydrocarbon growth precursor. Here we report on atomic scale simulations of cap nucleation of single-walled carbon nanotubes from hydrocarbon precursors. The presented mechanism emphasizes the important role of hydrogen in the nucleation process, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 65 publications
5
68
0
1
Order By: Relevance
“…The particle size was intentionally kept smaller and the reaction conditions, such as carbon precursor pressure, more aggressive in the simulations than in the experiment in order to decrease the calculation time needed to observe complete events from the simulations. We note that recent advances on accelerated molecular dynamics and hyperdynamics simulations have been reported and new methodologies are currently being developed such as collective variable-driven hyperdynamics (CVHD) [38] or hybrid approaches that combine reactive molecular dynamics with time-stamp force-bias Monte Carlo simulations [39], both of which could satisfactorily reproduce the dynamic behavior of reactive systems up to time scales of seconds without altering reaction conditions [38]. Previous studies using the current approach have shown that the mechanisms of nucleation and growth are the same for different particle sizes [18].…”
Section: Resultsmentioning
confidence: 99%
“…The particle size was intentionally kept smaller and the reaction conditions, such as carbon precursor pressure, more aggressive in the simulations than in the experiment in order to decrease the calculation time needed to observe complete events from the simulations. We note that recent advances on accelerated molecular dynamics and hyperdynamics simulations have been reported and new methodologies are currently being developed such as collective variable-driven hyperdynamics (CVHD) [38] or hybrid approaches that combine reactive molecular dynamics with time-stamp force-bias Monte Carlo simulations [39], both of which could satisfactorily reproduce the dynamic behavior of reactive systems up to time scales of seconds without altering reaction conditions [38]. Previous studies using the current approach have shown that the mechanisms of nucleation and growth are the same for different particle sizes [18].…”
Section: Resultsmentioning
confidence: 99%
“…Taking this opportunity accordingly, considerable roles of simulation and modeling studies played in really understanding growth and formation mechanisms of carbon nanostructures have to be validly recognized. A variety of computational techniques including quantum mechanical, tight-binding, and classical approaches have been applied to simulate the formation of endohedral fullerenes (Ohno et al 1996;Shiga et al 2001;Neyts and Bogaerts 2009) and the growth of CNTs (Ding et al 2008;Zhu et al 2010;Shibuta 2011;Neyts 2012;Khalilov et al 2015) and graphene (Meng et al 2012). While most of these simulations are limited to the TCVD case as for the latter, all of the described studies are instructive and useful for the understanding of PECVD growth.…”
Section: History Of Plasma-processing Growth and Formation Of Carbon mentioning
confidence: 99%
“…Since these species affect deposition and etching processes in combination with plasma-sheath electric fields, plasma-processing situations in real plasmas are highly complicated and likely to be uncontrollable or challenging from the simulation point of view. Recently, efforts to simulate the PECVD process of nanocarbon growth have been energetically tackled (Neyts 2012;Khalilov et al 2015).…”
Section: History Of Plasma-processing Growth and Formation Of Carbon mentioning
confidence: 99%
“…Only recently, the first simulations yielding a specific chirality were reported . Also recently, the first MD simulations appeared where growth was accomplished from actual hydrocarbon molecules instead of starting from atomic carbon …”
Section: Selected Applicationsmentioning
confidence: 99%